IDENTIFICAÇÃO DO NÍVEL DE COMPACTAÇÃO DO SOLO EM PASTAGEM DE TIFTON 85 IRRIGADO - Uhde, Leonir T.; Fernandes, Sandra B. V.; Londero, Ana L.; Rupollo, Carlos Z.; Porazzi, Cláudio C. (Salão do Conhecimento, 2013)
Resumo